2019
DOI: 10.1002/chem.201903684
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Ag Nanocrystals in a H‐Bonded Open Framework

Abstract: A procedure that enabled rational access to the first example of hybrid material made of NPs grown within a H‐bonded framework is reported. To avoid competitive reactions with the framework units, the metal precursor was chemically trapped in the porous structure and subsequently photo‐reduced to afford the hybrid material Ag@SPA‐2, which consists of Ag NPs of nanometric sizes (<15 nm) homogeneously distributed in the crystals of the host material. In a subsequent step, taking advantage of the porous matrix th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Supramolecular porous architectures (SPA hereafter) with large pores have been achieved, including a material with channels decorated by basic pyridyl groups capable to efficiently adsorb acidic molecules, [62] or to template the growth of metal nanoparticles. [63] In the course of these investigations, a SPA with very robust structure, showing 1D channels ( ca 8.5 Å of apparent diameter), has been identified. [61] This solid, SPA‐1(H), results from the 2 : 1 assembly between [H 3 ‐TripCH 2 ‐R] 3+ tripodal cations with R=H and [Zr 2 (Ox) 7 ] 6− complexes (Ox=(C 2 O 4 ) 2− , Scheme 1 ).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Supramolecular porous architectures (SPA hereafter) with large pores have been achieved, including a material with channels decorated by basic pyridyl groups capable to efficiently adsorb acidic molecules, [62] or to template the growth of metal nanoparticles. [63] In the course of these investigations, a SPA with very robust structure, showing 1D channels ( ca 8.5 Å of apparent diameter), has been identified. [61] This solid, SPA‐1(H), results from the 2 : 1 assembly between [H 3 ‐TripCH 2 ‐R] 3+ tripodal cations with R=H and [Zr 2 (Ox) 7 ] 6− complexes (Ox=(C 2 O 4 ) 2− , Scheme 1 ).…”
Section: Introductionmentioning
confidence: 93%
“…(m 2 • g À 1 ) [b] exp. (m 2 • g À 1 ) [d] (cm 3 [a] Mercury void calculation; [63,65] [b] Total pore volume or surface area calculated from the single XRD data and the void estimation; [c] Total pore volume measured at P = 1 atm; [d] Surface area calculated assuming a Langmuir model for the CO 2 adsorption isotherm. Chemistry-A European Journal sorption isotherms fall between those found for SPA-1(OH) and SPA-1(CH 3 ).…”
Section: H 2 O Sorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the hydrogen-bond networks can provide hydrogen-bond sites that interact weakly with volatile carbonyl compounds. The characteristics of metal-complex-based hydrogen-bond networks have been investigated for more than two decades (for selected reviews, see refs ; for recent examples, see refs ); nevertheless, the adsorption/desorption properties of volatile carbonyl compounds in such networks have not been explored, except in the case of acetone. Takamizawa et al have measured the adsorption isotherm of acetone in a hydrogen-bond network derived from [Co­(ethylenediamine) 3 ]­Cl 3 . The Beatty group has investigated the desorption of co-crystallized acetone from the crystals of [M­(2,4-pyridine dicarboxylate) 2 ] 2– , where M was Cu or Zn. , Castillo and co-workers have confirmed that a [Cu 2 (μ-adenine) 4 Cl 2 ]­Cl 2 -based hydrogen-bond network can adsorb acetone .…”
Section: Introductionmentioning
confidence: 99%